Study to assess proper timing of laryngoscopy in post-thyroid surgery patients to detect recurrent laryngeal nerve injury - Tausif Ahmed (Manipal College of Medical Sciences, Pokhara, 2021)
Background: Thyroid surgeries are commonly done nowadays for benign and malignant conditions. Recurrent laryngeal nerve palsy (RLNP) is an important and potentially catastrophic complication of thyroid surgery. The purpose of the study was to determine the impact of rigid endoscopy (Hopkins rod-lens telescope) performed at different time intervals on the diagnosis of RLNP in post-thyroid surgery patients.